2019
DOI: 10.3390/polym11050805
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic Polytetrafluoroethylene/Heat-Shrinkable Polyvinyl Chloride Composite Film with Super Anti-Icing Property

Abstract: Wind power generation is an environmentally friendly way to produce electricity, but wind turbine blades that are prone to freeze in winter will reduce the efficiency of the generator. Therefore, the preparation of anti-icing blades is important and essential. Herein, anti-icing polytetrafluoroethylene (PTFE)/heat-shrinkable polyvinyl chloride (HSPVC) composite film was prepared by depositing a PTFE coating on the surface of HSPVC film via vacuum thermal evaporation. HSPVC films were pretreated respectively by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Two methods have been utilized to cover the surfaces with PTFE: the deposition of PTFE-like layers using magnetron sputtering and surface fluorination via the plasma-assisted chemical vapor deposition of tetrafluoroethane (C 2 H 2 F 4 ) or plasma treatment in sulfur hexafluoride (SF 6 ) discharge. The results showed that the surfaces exhibited significant improvement in hydrophobicity [40,41] and antimicrobial properties [42].…”
Section: Introductionmentioning
confidence: 99%
“…Two methods have been utilized to cover the surfaces with PTFE: the deposition of PTFE-like layers using magnetron sputtering and surface fluorination via the plasma-assisted chemical vapor deposition of tetrafluoroethane (C 2 H 2 F 4 ) or plasma treatment in sulfur hexafluoride (SF 6 ) discharge. The results showed that the surfaces exhibited significant improvement in hydrophobicity [40,41] and antimicrobial properties [42].…”
Section: Introductionmentioning
confidence: 99%
“…Superhydrophobic coatings have aroused diverse interest because of a wide range of applications in self-cleaning, anticorrosion, , sensing, flexible wearable devices, drag reduction, , oil–water separation, , anti-icing, , detection, and so on. However, the loss of the superhydrophobic property of the coatings after prolonged use in practical applications is still a serious problem.…”
Section: Introductionmentioning
confidence: 99%
“…Water droplets on the superhydrophobic coating keep almost spherical, significantly reducing the contact area and adhesion force between the superhydrophobic surface and water droplets [ 1 , 2 ]. Therefore, superhydrophobic coatings are widely used in self-cleaning [ 3 , 4 ], oil-water separation [ 5 , 6 ], anti-icing [ 7 , 8 ], leakage current suppression [ 9 ], and other aspects.…”
Section: Introductionmentioning
confidence: 99%